Synthesis and Antimicrobial Activity of 3-Amino-5-aryl/alkylimino-1,2,4-thiadiazolines - V. GANDHE, SHITAL; BERAD, B.N. (Asian Journal of Chemistry, 2010)
The 3-amino-5-aryl/alkyl imino-1,2,4-thiadiazolines (IV) have been synthesized by the oxidative cyclization of 1-amidino-3-aryl/alkyl thiocarbamides (II) with iodine followed by basification. The thiocarbamides (II) were prepared by refluxing the mixture of guanidine nitrate and aryl/alkyl isothiocyanates (I) in ethanolic sodium hydroxide solution. the title compounds on acetylation with acetic anhydride (1:1) in glacial acetic acid afforded monoacetyl derivatives (V). The structures of all these compounds were confirmed on the basis of elemental analysis and spectral data and assayed for their antimicrobial activity against gram-positive as well as gram-negative micro-organisms.